Land Suitability Analysis of Mung Bean Plants (Vigna radiate L.) by Growing Degree Days Method - Yanti, Delvi; Ramanda, Rian; Safitri, Imelda (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2024)
Mung bean (Vigna radiate L.) is one of the most widely cultivated crops after soybean and peanut. Mung beans (Vigna radiate L.) became one of the crops that experienced a decline in production amid the increase in the area of harvested land in West Sumatra. The purpose of this study was to analyze the level of land suitability of mung bean crops using the Growing Degree Days method in West Sumatra Province. The research method used in this research is Scoring and Overlay using ArcGis 10.5 software. Land suitability analysis is carried out by giving scores to several parameters of land characteristics. The parameters used are slope, land use, rainfall, soil texture and soil pH. Growing Degree Days analysis was conducted by accumulating the daily temperature values of plants based on planting scenarios. These two analyses were combined with Overlay clustering. The results showed that the land area of West Sumatra whose GDD value is optimal for mung bean growth with the level of land suitability in physical characteristics in S1 class is 15,819.29 ha and in S2 class is 877,501.06 ha. Areas that are suitable in terms of physical characteristics and values with an area of > 100 ha are Lima Puluh Kota District, Pasaman District, Solok District, and South Solok District. The best planting time for mung bean based on the planting scenario is from December to March.